2003
DOI: 10.1023/a:1022837810357
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Immunoreactivities (IR) for catecholamine-synthesizing enzymes tyrosine hydroxylase (TH), dopamine-beta-hydroxylase (DbetaH), phenylethanolamine N-methyl transferase (PNMT), serotonin-synthesizing enzyme tryptophan hydroxylase, and neuropeptide Y were investigated in the intrinsic cardiac nervous system of 27-40-day-old rats using fluorescent immunohistochemistry. Individual neurons were identified by the general neuronal marker protein gene product 9.5. The presence of DbetaH and PNMT in the atrial specimens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…However, there is certainly some species-variability in neurochemistry, and the evidence for a complete adrenergic panel in one species is debatable. Based on these data, however, some investigators have suggested that a pure adrenergic population, or a dual cholinergic/adrenergic population, may reside with cell bodies actually present within the cardiac ganglia 17 , 348 - 355 . At least in the rat, we were able to definitively demonstrate that glyoxcylic acid histofluorescence for catecholamines was absent from large (20–40 μm diameter) cardiac ganglion neurons, but was present in small (8–10 μm) intensely fluorescent (SIF) cells 199 .…”
Section: Adult Plasticity In Cardiac Autonomic Neuronsmentioning
confidence: 99%
“…However, there is certainly some species-variability in neurochemistry, and the evidence for a complete adrenergic panel in one species is debatable. Based on these data, however, some investigators have suggested that a pure adrenergic population, or a dual cholinergic/adrenergic population, may reside with cell bodies actually present within the cardiac ganglia 17 , 348 - 355 . At least in the rat, we were able to definitively demonstrate that glyoxcylic acid histofluorescence for catecholamines was absent from large (20–40 μm diameter) cardiac ganglion neurons, but was present in small (8–10 μm) intensely fluorescent (SIF) cells 199 .…”
Section: Adult Plasticity In Cardiac Autonomic Neuronsmentioning
confidence: 99%
“…The regulation of the heart function by the autonomic nervous system has two main components: an adrenergic component, which stimulates the heart and conduction system, and a cholinergic component, which inhibits them [29,30]. It is also known that the sympathetic part consists mainly of nerve fibers, while the parasympathetic part involves both fibers and nerve cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is a biochemically and functionally very heterogeneous group of interconnected neurons containing both cholinergic and adrenergic neurons. These neurons contain in addition to classical mediator also one or more neuropeptides ( Slavikova et al, 2003 ). All together are responsible for integration of sensory information from the heart with information coming from CNS ( Kukanova and Mravec, 2006 ).…”
Section: Discussionmentioning
confidence: 99%